Manajemen Komunikasi Sebagai Upaya Menjaga Harmonisasi Kerukunan Umat Beragama Di Desa Rama Agung Bengkulu Utara - Alfarabi, Alfarabi; Agustina, Putri Rizki; Putra, Delfan Eko (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2024)
Socioculturally, the Rama Agung village community is generally predominantly influenced by the legacy of ancestral values, regulations, and customary laws, as well as past traditions brought and adopted from various ethnic groups. Communication will be better established when someone can see broadly and openly the contexts of tolerance in diversity. This study aims to determine the communication management carried out by the Rama Agung community in maintaining harmony between religious communities. This study uses a qualitative method. The results of the study concluded that the Harmonization that occurred in Rama Agung was maintained because of the values ??of harmony instilled by the community in inter-religious life, namely the existence of open communication between fellow believers, mutual respect for other religious celebrations and mutual respect for the rules of other religions. The communication management carried out by the Rama Agung community in maintaining harmony in inter-religious life is in accordance with the convergence and divergence approaches. The communication management carried out by the Rama Agung community uses communication that maintains feelings to realize effective communication in maintaining harmony in inter-religious life.